Research Determination of the Number of Workforce Needs in 2025 at Badan Pengelola Tabungan Perumahan Rakyat (BP Tapera) Using the Workload Analysis Method - Karya Bakti Kaban (MANAGER: Journal of Management and Administration Science, 2025)
In the era of globalization, organizations are required to operate efficiently and professionally. However, mismatches between employee competencies and job roles, as well as uneven employee distribution, remain common issues. This study applies the Workload Analysis (WLA) method to determine the optimal number of employees by assessing working hours, task volume, and standard time. The analysis involved identifying all tasks performed by employees, measuring their physical and mental workload, and comparing it to individual work capacity. The case study was conducted at BP Tapera, which comprises 12 directorates, 1 secretariat, and 1 internal supervisory unit. Of the 185 employees, 59 (32%) were underloaded, 83 (45%) were in a normal/fit category, and 34 (18%) were overloaded, while 9 employees (5%) were not assessed due to recent employment. The projected workforce need for 2025 is 63 additional employees, with the highest demand in the Directorate of Membership (12 employees). The findings highlight the importance of aligning human resources with organizational needs through effective workload distribution, job description refinement, and competency development. This study provides a practical basis for strategic workforce planning and enhancing overall organizational productivity.